SEJARAH MAKANAN DI INDONESIA DALAM PERSPEKTIF GLOBAL - , Fadly Rahman; , Dr. Sri Margana, M. Phil. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The food image in Indonesia is known by its cultural varieties, uniqueness, and rich on taste. Those are shaped through the long historical process (longue durÃ©e) and also influenced by global elements. This study discusses on food history of Indonesia in global perspective. The subject of this study is observing the dynamics of the food development in Indonesia. This study aimed to comprehend the historical elements which shaped the development of food image in Indonesia. Those elements are including food cultivation, politic, economy, and culture that observed its interconnection. This study employs historical method by approach the global history perspective and supported by various primary and secondary sources including cookbooks, food sciences, monographs, itinerary reports, archives, magazines, newspaper, and private document. The findings of this study i.e. first, the historical root of food formation in Indonesia had transpired since the ancient time that indicated by the efforts of ancient society in inventing-invention various foods that utilized the sources in surround them. Second, the entry of various global influences (from China, India, Arab, and Europe) until 18th century also followed by the entry of sorts of new foodstuffs (plant and animal) that then influenced the food evolution. Third, the development of foods cultivation since 19th century until early of 20th century influenced the development of food sciences and gastronomy culture as a form of food innovation (nouvelle cuisine) that marked by the creation of Indische keuken. Fourth, the times of malaise, Japanese power and Indonesian Independence were the fading periods for Indische keuken. Fifth, the composing of Indonesian cookbookâs Mustika Rasa was a deconstruction effort to the Indische keuken. This study concludes that the food development in Indonesia is a continuity phase of former development in ancient time and colonial time that transpired in the process of inventing-invention and innovation of food.